Construction development and its impact on the construction enterprises financial results - Pavelko, Olha; Lazaryshyna, Inna; Dukhnovska, Liudmyla; Sharova, Svitlana; Oliіnyk, Tetіana; Donenko, Iryna (My University, 2021)
The article aims to monitor the construction development dynamics in Ukraine in recent years and substantiate its impact on the construction enterprises' financial results in general. The existing factors of development of construction in Ukraine are analyzed. The following groups: political, raw, industrial, environmental, consumer, infrastructure and investment, macroeconomic, financial, social, and innovative are identified. The influence of the factors mentioned above on the financial results of construction enterprises activity and the generating factors - income and expenses- is revealed. It was established that construction has become more active in recent years, with the highest residential and non-residential construction rates and the engineering structures construction in 2016, which were observed in Kyiv. Each year, the largest capital investments are characterized by engineering structures, in contrast to residential and non-residential buildings. The maximization of income and cost minimization make for improving the efficiency of the management of construction enterprises, which represents their ultimate goal. The conducted research gives reasons to state the significant role of the country macroeconomic environment in the construction enterprises functioning and the purport of their financial results. Construction development directions in the present conditions, the methodology, and construction enterprise accounting organization are covered.
Keywords: construction; accounting; building enterprise; profit